PERAN DINAS TENAGA KERJA DALAM UPAYA MENGURANGI MASALAH PENGANGGURAN TERDIDIK DI WILAYAH KOTA SURAKARTA - Nurrussyita, Sela; Wirawan, Riska (Solidaritas, 2025)
Educated unemployment is a complex problem faced by many cities, including Surakarta. Ironically, most of the unemployed in Surakarta are those who have a fairly high level of education, namely high school and diploma or bachelor's level. One of the causes of the large number of educated unemployed is the mismatch between skills and labor market needs and individual factors themselves. This study aims to determine the role of the Manpower Office in efforts to reduce the problem of educated unemployment in the Surakarta City area.This study uses the theory according to Gede Diva (2019:15-18) that the role of local government as a Regulator, Facilitator and Catalyst. This study uses a descriptive qualitative method. Data collection used is interviews, documentation, and observation. The analysis techniques used are data collection, data condensation, data presentation and drawing conclusions.The results of the study indicate that the Surakarta City Manpower Office has an important role in reducing educated unemployment through programs and activities, these programs include job training by organizing job training aimed at improving the skills and competencies of job seekers to match the needs of the labor market. Job fairs, namely by facilitating meetings between job seekers and companies through job fairs. The Manpower Office provides accurate and up-to-date job market information to educated job seekers. Cooperation with companies by establishing cooperation with companies to provide job opportunities for educated job seekers. Keywords: Department of Manpower, Role, Educated Unemployment